Critical Thinking Skills Reviewed from Logical-Mathematical and Musical Intelligence on Process Oriented Guided Inquiry Learning - Rifqi, Ainur; Rochmad, Rochmad; Suyitno, Hardi (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe critical thinking skill reviewed from logical-mathematical and musical intelligence. This mix method research used sequential explanatory design. The subjects consisted of 35 X AKL3 students of Islamiyah VHS, Sapugarut, Pekalongan municipality, in academic year 2019/2020. They were selected based on categories, such as high logical -mathematical intelligence and low musical intelligence, low logical - mathematical intelligence and high musical intelligence, and high logical - mathematical and musical intelligences. The findings showed that the students’ mathematics critical students with high logical-mathematical and low musical intelligence met all indicators of interpreting problem, applying solution, evaluating solution, and concluding the results by using facts. The students’ mathematics critical thinking skill with low mathematical intelligence and high musical intelligence met all indicators of interpreting problems, applying solution, and evaluating the solution. The mathematics critical thinking skill of students with high logical-mathematical and musical intelligence could met all indicators of interpreting problems, applying solution, evaluating solution, and concluding the results by using facts.